2019
DOI: 10.1007/s13201-019-1088-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater quality status by using water quality index (WQI) and geographic information system (GIS) approaches: a case study of the Bokaro district, India

Abstract: One hundred two groundwater samples were collected from the Bokaro district of Jharkhand state, India, during the pre-and post-monsoon seasons of the year 2014-2015. In the present study, groundwater samples were analysed for pH, TDS, TH,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(39 citation statements)
references
References 21 publications
3
35
0
1
Order By: Relevance
“…− , Cu, Ni, Pb, and Zn concentrations that resulted from anthropogenic activities (agriculture, house holding, and industry) [23,64]. Some studies on groundwater from Asia (Bokaro district, India) and Africa (Bonkoukou, Niger) indicated high values for the WQI (>150), showing inadequacy for drinking purposes or poor quality, due to the anthropogenic activities (agricultural waste, untreated domestic waters), but also due to natural processes (rock weathering, intrusion of sea water) [65][66][67][68]. In Europe, studies on karstic waters in the Megara basin, Greece indicated generally good water quality (WQI < 100) with few cases of poor water quality [5].…”
Section: Water Quality Indicesmentioning
confidence: 99%
“…− , Cu, Ni, Pb, and Zn concentrations that resulted from anthropogenic activities (agriculture, house holding, and industry) [23,64]. Some studies on groundwater from Asia (Bokaro district, India) and Africa (Bonkoukou, Niger) indicated high values for the WQI (>150), showing inadequacy for drinking purposes or poor quality, due to the anthropogenic activities (agricultural waste, untreated domestic waters), but also due to natural processes (rock weathering, intrusion of sea water) [65][66][67][68]. In Europe, studies on karstic waters in the Megara basin, Greece indicated generally good water quality (WQI < 100) with few cases of poor water quality [5].…”
Section: Water Quality Indicesmentioning
confidence: 99%
“…This technique is used to decrease the large amount of water quality parameters in a single numerical value to assess groundwater quality status. This method has been used in many groundwater analysis studies [35][36][37][38][39][40] In general, there are 3 main steps required to develop the WQI. These steps are assigning weights, calculating rating scale and aggregation of sub-indices to produce the final index.…”
Section: Groundwater Quality Indexmentioning
confidence: 99%
“…Verma et al [12] assessed the suitability of groundwater for potable purpose by the human beings by considering groundwater samples with twelve physical and chemical parameters that are T-hard, TDS, pH, calcium and Magnesium etc., collected during two seasons pre monsoon and post monsoon in the year 2014-2015 from Bokaro district, Jharkhand State, India. The Geographic information system based on water quality index model implemented to ascertain the groundwater quality.…”
Section: Literature Surveymentioning
confidence: 99%